Government Support for Universities: Regional Coverage - V. L. Parkacheva; I. B. Trostyanskaya; E. G. Grishakina; N. A. Polikhina (Высшее образование в России, 2022)
The aim of the study is to assess the degree of involvement of various Russian regions in the implementation of governmental projects for university support, which is essential for the balanced development of national higher education system and the spatial development of the country as a whole. The task of effectively using the research and educational potential of universities for the development of particular regions is currently being under realization in many countries, including Russia, which determines the relevance of this study. The analysis is based on the quadrant distribution of national regions in the Federal State Statistics Service Rankings 2018 on regional GDP, the Regional Innovation Development Rankings 2018–2019, issued by the Higher School of Economics. We compared universities located in regions with similar characteristics of their economic development, and assessed the impact of 11 major governmental projects for university support, which have been implemented or continue since 2006. The study is targeted at tracking correlations between the regional distribution of universities supported by these projects, the amounts of funding, and the scales of innovation and economic development of the regions. We conclude that at present, in comparison with previous periods, a more balanced approach is being taken to the selection of universities-participants of such government projects from the point of view of their location in regions with different characteristics. At the same time, the distribution of financial support points to the existing serious gaps between the leading and other universities.